Imprints of Quasi‐Adiabatic Ion Dynamics on the Current Sheet Structures Observed in the Martian Magnetotail by MAVEN. Issue 10 (19th October 2017) - Grigorenko, E. E.; Shuvalov, S. D.; Malova, H. V.; Dubinin, E.; Popov, V. Yu.; Zelenyi, L. M.; Espley, J.; McFadden, J. P.
Abstract: Numerous studies of the current sheets (CS) in the Earth's magnetotail showed that quasi‐adiabatic ion dynamics plays an important role in the formation of complicated multilayered current structures. In order to check whether the similar mechanisms operate in the Martian magnetotail, we analyzed 80 CS crossings using MAVEN measurements on the nightside of Mars at radial distances 1.0–2.8 R M . We found that CS structures experience similar dependence on the value of the normal component of the magnetic field at the neutral plane ( B N ) and on the ratio of the ion drift velocity outside the CS to the thermal velocity ( V T / V D ) as it was observed for the CSs in the Earth's magnetotail. For the small values of B N, a thin and intense CS embedded in a thicker one is observed. The half‐thickness L of this layer is 30–100 km ≤ ρH+ (ρH+ is a gyroradius of thermal protons outside the CS). With the increase of B N, the L also increases up to several hundred kilometers ( ρO+, ρO2+ ), the current density decreases, and the embedding feature disappears. Our statistical analysis showed a good agreement between L values observed by MAVEN and the CS scaling obtained from the quasi‐adiabatic model, if the plasma characteristics in Martian CSs are used as input parameters. Thus, we may conclude that in spite of the differences in magnetic topology, ion composition, and plasma thermal characteristics observed in the Earth's and Martian magnetotails, similar quasi‐adiabatic mechanisms contribute to the formation of the CSs in the magnetotails of both planets. Key Points: Thin and intense current layers with a half‐thickness L of 30–100 km ≤ ρH+ embedded in a thicker CSs are observed in the Martian magnetotail The embedded current layers can be explained by quasi‐adiabatic dynamics of multicomponent ion population The CS thickness depends on B N / B 0 and on V T / V D of the dominant ion component in agreement with the quasi‐adiabatic scaling law